2020
DOI: 10.3390/w12051466
|View full text |Cite
|
Sign up to set email alerts
|

Flood Risk Evaluation in Ungauged Coastal Areas: The Case Study of Ippocampo (Southern Italy)

Abstract: The growing concentration of population and the related increase in human activities in coastal areas require numerical simulations to analyze the effects of flooding events that might occur in susceptible coastal areas in order to determine effective coastal management practices and safety measures to safeguard the inhabited coastal areas. The reliability of the analysis is dependent on the correct evaluation of key inputs such as return period of flooding events, vulnerability of exposed assets, and other ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 54 publications
1
29
0
Order By: Relevance
“…Furthermore, because of a strongly interconnected rainfall-runoff process, as well as a rapid advancement of computational technology and the availability of high-resolution topographic data [3], pluvial floods are now simulated using integrated hydrological-hydraulic methods consisting of time-dependent 2D models and so-called rain-on-grid approaches [2,[4][5][6][7]. However, a reliable flood prediction in small ungauged catchments remains difficult because of the lack of field observations needed to calibrate models [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, because of a strongly interconnected rainfall-runoff process, as well as a rapid advancement of computational technology and the availability of high-resolution topographic data [3], pluvial floods are now simulated using integrated hydrological-hydraulic methods consisting of time-dependent 2D models and so-called rain-on-grid approaches [2,[4][5][6][7]. However, a reliable flood prediction in small ungauged catchments remains difficult because of the lack of field observations needed to calibrate models [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Apollonio et al 2020 stated that the reliability of flood risk assessment depends on key inputs such as the return period and the spatial distribution of elements. Accordingly, they distributed element structures, infrastructure as input, buildings, other structures, roads, and specialized/unspecialized land use as output [37]. In this study, a similar assumption was accepted.…”
Section: Data Collection-processing-analysismentioning
confidence: 81%
“…South America (5%) [37][38][39][40][41] and Africa (4%) [42][43][44][45][46] showed less research interest (Figure 2). Following a detailed analysis of each region, we found that the most researched areas were: the United States, representing 13.19% of the total articles analyzed and 71.72% of the articles located in North America [47][48][49]; the United Kingdom, with 90 articles representing 17.92% of the articles in Europe and 6.78% of the total papers [50][51][52]; Italy and Spain, accounting for 5.27% of the entire articles and 13.94% of the scientific papers published in Europe, respectively [53][54][55]; and China, accounting for 5.27% of the total articles and 20.11% of the articles in Asia [56][57][58]. A significant percentage of publications also came from India, representing 16.6% of all Asian scientific articles and 4.37% of the total publications [59][60][61].…”
Section: Spatial Distribution Of Researchmentioning
confidence: 82%